Marine Citizen Science: Recent Developments and Future Recommendations. (30th November 2020) - Sandahl, Andrew; Tøttrup, Anders P.
Marine Citizen Science (MCS) is highly underrepresented in the citizen science literature, despite the instrumental (data-focused) and capacity-building (society-focused) benefits such projects offer for marine conservation. Nevertheless, the MCS literature has experienced continual growth since its first publications in the early 1990s. Few reviews have considered the developing history of MCS, and none have considered recent developments in the field. By reviewing 185 MCS papers published from 2014–2018, this study examines recent developments in MCS and offers informed recommendations for future MCS projects. Over the five surveyed years, there were significant increasing trends in both MCS publication quantity and diversity of affiliated research countries, although many tropical study regions with high observation potential remained underrepresented. Sixty-eight percent (68%, N = 126) of surveyed MCS studies focused on non-emblematic study subjects versus thirty-two percent (32%, N = 59) of studies that focused on emblematic subjects (e.g., coral reefs, megafauna, and endangered/critically endangered species found on the Red List of Threatened Species compiled by the International Union for Conservation of Nature [IUCN]), suggesting that the charismatic appeal of the scientific topic may not be a limiting factor to volunteer participation. Nearly 82% (N = 151) of studies failed to describe explicit hypotheses, and many studies utilizing novel data neglected to include descriptions of data quality assurance measures (25%, N = 47) in their reports, potentially fueling the credibility challenge, which citizen science research faces as a whole. Finally, only a small portion of studies (10%, N = 19) involved participants beyond mere data collection, despite the unique and diverse perspectives volunteers may bring to scientific research. Collectively, these results aid in forming a set of recommendations for future MCS projects seeking to improve the quality of their credibility, study design, and volunteer contributions through explicitly stating hypotheses/quality-insurance methods, considering the potential of non-emblematic study species/smartphone applications, and designing projects that allow for a spectrum of volunteer participation in high-observation potential areas.